Discovery of the pre-main-sequence eclipsing binary MML 48 - Gómez Maqueo Chew, Y. (2025)
Aims. We present the discovery of the eclipsing binary MML 48, which is a member of Upper Centaurus Lupus, has an associated age of 16 Myr, and is composed of two young, low-mass stars.Methods. We used space- and ground-based observations to characterize the system with both time-series photometry and spectroscopy. Given the extreme mass ratio between the stars, qEB = 0.209 ± 0.014, we modeled a single-lined spectroscopic and eclipsing binary system.Results. The orbital period, 2.0171068 ± 0.0000004 d, is measured from the highest precision light curves. We derive a primary mass of 1.2 ± 0.07 M⊙ using stellar models, and with radial velocities we measured a secondary mass of 0.2509 ± 0.0078 M⊙ . The radii are large, as expected for pre-main-sequence stars, and are measured as 1.574 ± 0.026 ± 0.050 R⊙ and 0.587 ± 0.0095 ± 0.050 R⊙, for the primary and secondary stars, respectively.Conclusions. MML 48 joins the short list of known low-mass, pre-main-sequence eclipsing binaries (EBs), being one of only five systems with intermediate ages (15-25 Myr), and the system with the most extreme mass ratio. The primary star is currently at the “fusion bump", undergoing an over-production of energy in the core due to the build-up of He before reaching its equilibrium abundance set by the proton-proton (p-p) I chain. MML 48 A is the first young star in an eclipsing system that has been found during its fusion bump. MML 48 is thus an important benchmark for low-mass stellar evolution at a time when the stars are rapidly changing, which allows for a tight constraint on the corresponding isochrone given the uneven mass ratio.